2015
DOI: 10.1093/hmg/ddv439
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis and denervation alter sphingolipids and up-regulate glucosylceramide synthase

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal adult-onset disease characterized by upper and lower motor neuron degeneration, muscle wasting and paralysis. Growing evidence suggests a link between changes in lipid metabolism and ALS. Here, we used UPLC/TOF-MS to survey the lipidome in SOD1(G86R) mice, a model of ALS. Significant changes in lipid expression were evident in spinal cord and skeletal muscle before overt neuropathology. In silico analysis also revealed appreciable changes in sphingolipids includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 64 publications
5
88
1
Order By: Relevance
“…Alterations in sphingolipids have been associated with a wide variety of neurodegenerative diseases. Several sphingolipids serve as bioactive signaling molecules in a plethora of pathways and have been implicated in Alzheimer's (48,49), Parkinson's (50), and ALS (51). We sought to determine if changes in sphingolipid metabolism may mediate CMT phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in sphingolipids have been associated with a wide variety of neurodegenerative diseases. Several sphingolipids serve as bioactive signaling molecules in a plethora of pathways and have been implicated in Alzheimer's (48,49), Parkinson's (50), and ALS (51). We sought to determine if changes in sphingolipid metabolism may mediate CMT phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…GlcCer and downstream gangliosides were analysed as described previously 13 . Tissues were homogenized in water using an Ultraturax T25 probe homogenizer (IKA, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, inhibition of GlcCer synthesis caused impaired nerve regeneration after peripheral nerve injury and was highly deleterious in SOD1 G86R mice 13, 14 . The expression of ugcg , a gene encoding the enzyme catalysing the first step of glycosphingolipid synthesis, was strongly upregulated in muscle biopsies of ALS patients, independent of disease severity, suggesting a dysregulation in glycosphingolipid homeostasis in ALS at early disease stage.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was an enrichment of glucosphingolipid metabolism in Tg-SOD1 G86R mice (Henriques et al, 2018). Another study confirmed the downregulation of sphingolipids and the upregulation of glucosylceramides (Henriques et al, 2015). In the blood of Tg-SOD1 G93A mice, the concentration of 12-hydroxyeicosatetranoic acid (12-HETE), a derivative of the lipoxygenase pathway, has been found to be increased, when the symptoms of ALS appear (Trostchansky et al, 2016).…”
Section: Lipidomicsmentioning
confidence: 86%